Strengthening Children's Motor Intelligence through The Learning Management System - Anita Kusumaningrum; Fathor Rozi; Hasan Baharun; Yulis Mutiatun; Niswatun Mardiyah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to analyze age and understand online learning in early childhood with the help of Whatsapp video calls to improve motor intelligence. This research uses a case study type approach to get an idea of Whatsapp video call-assisted learning in improving motor intelligence in early childhood, observing and documenting learning activities at the institution. Interviews were conducted with principals, teachers, and guardians of students. This research was conducted at RA Mambaul Irfan, Asembakor, Kraksaan, Probolinggo. The results showed that the strategy for the teacher to improve motor intelligence at an early age through Whatsapp video calls was carried out through; Planning, Program Implementation, and Evaluation. This study appreciates that teacher innovation with various media can be carried out even in pandemic conditions, such as WhatsApp video call media